Privatisation and corporate governance in emerging economies: What went wrong with Aguas Argentinas S.A.?. (30th March 2010) - Porporato, Marcela; Robbins, Peter T.
Here is explored corporate governance role in privatised water companies in emerging economies. Private parts contracts are periodically renegotiated due to externalities and information asymmetries. In this context, governance mechanisms are of critical importance as illustrated in the case study of the city of Buenos Aires where water services privatised in 1993 were re-nationalised in 2006. The failure is traced to regulations, including the regulatory control body, coupled with the company's reluctance of having transparent and open governance mechanisms. The failure is linked with fuzzy and weak corporate governance, a common problem in emerging economies eager to attract private investors.